Design and synthesis of fluconazole/bile acid conjugate using click reaction - Pore, Vandana S.; Aher, Nilkanth G.; Kumar, Manish; Shukla, Praveen K. (Tetrahedron, 2006)
Novel fluconazole/bile acid conjugates were designed and their regioselective synthesis was achieved in very high yield via Cu(I) catalyzed intermolecular 1,3-dipolar cycloaddition. These new molecules showed good antifungal activity against Candida species. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Click chemistry; fluconazole/bile acid conjugate

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Design, synthesis, and micellar properties of bile acid dimers and oligomers linked with a 1,2,3-triazole ring - Aher, Nilkanth G.; Pore, Vandana S.; Patil, Sachin P. (Tetrahedron, 2007)
1,3-Dipolar cycloaddition of propargyl esters of bile acids to azide group attached at different positions of bile acids gave dimers, trimer, and tetramer linked with 1,2,3-triazole. These dimeric and oligomeric structures were able to solubilize hydrophilic dye-cresol red, in nonpolar solvent. (c) 2007 Elsevier Ltd. All rights reserved.

Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Design and synthesis of bile acid-based amino sterols as antimicrobial agents - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Shukla, Praveen K.; Gonnade, Rajesh G. (Bioorganic & Medicinal Chemistry Letters, 2009)
New bile acid-based amino sterols were synthesized in good yields from C-3 beta-oxiranes as key intermediates. These derivatives were evaluated for their in vitro antimicrobial properties against human pathogens. These compounds showed better antibacterial activity as compared to antifungal activity. Compounds 21 and 22 showed comparable antibacterial activity to gentamicin against Staphylococcus aureus with IC(50) values of 5.14 and 4.46 mu g/mL. This is the first report for the synthesis of C-3 beta-oxiranes on the steroids having A/B cis ring junction and these oxiranes have been used for the synthesis of amino sterols 17, 18, 21, and 22. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amino sterols; Antibacterial agent; bile acid; Oxirane

Stereoselective construction of steroidal side chain from 16-dehydropregnenolone acetate - Aher, Nilkanth G.; Gonnade, Rajesh G.; Pore, Vandana S. (Synlett, 2009)
Stereoselective construction of steroidal side chain at C-20 having `natural' configuration using 16-dehydropregnalone acetate (16-6PA) as a starting material has been carried out. Palladium-catalyzed carbon-carbon bond-forming Heck reaction between C-20 vinyl iodide with methyl acrylate and transfer hydrogenation with triethylsilane and Pd/C are the key steps for stereoselective side-chain synthesis.
Keywords: 16-dehydropregnenolone acetate; Heck coupling; stereoselectivity; steroidal side chain; transfer hydrogenation

Synthesis and antifungal activity of 1,2,3-triazole containing fluconazole analogues - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Kumar, Awanit; Shukla, Praveen K.; Sharma, Aanchal; Bhat, Manoj K. (Bioorganic & Medicinal Chemistry Letters, 2009)
Fluconazole based novel mimics containing 1,2,3-triazole were designed and synthesized as antifungal agents. Their antifungal activities were evaluated in vitro by measuring the minimal inhibitory concentrations (MICs). Compounds 12, 15, and 16 were found to be more potent against Candida fungal pathogens than control drugs fluconazole and amphotericin B. The studies presented here provide structural modi. cation of fluconazole to give 1,2,3-trazole containing molecules. Furthermore, these molecules were evaluated in vivo against Candida albicans intravenous challenge in Swiss mice and antiproliferative activities were tested against human hepatocellular carcinoma Hep3B and human epithelial carcinoma A431. It was found that compound 12 resulted in 97.4% reduction in fungal load in mice and did not show any profound proliferative effect at lower dose (0.001 mg/ml). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Conjugates; Fluconazole

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester

Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

RuCl3-TBHP mediated allylic oxidation of Delta(8(9)) lanosterol derivatives - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S. (Tetrahedron Letters, 2011)
A variety of Delta(8(9))-lanosterol derivatives were converted into 7,11-dienones using t-butyl hydroperoxide in the presence of ruthenium chloride (RuCl3) in good yields. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; Oxygenated steroids; Ruthenium chloride; Steroidal ketones; t-Butyl hydroperoxide

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Synthesis and antifungal activity of 1,5-disubstituted-1,2,3-triazole containing fluconazole analogues - Pore, Vandana S.; Jagtap, Manisha A.; Agalave, Sandip G.; Pandey, Atindra K.; Siddiqi, Mohammad I.; Kumar, Vikash; Shukla, Praveen K. (Medchemcomm, 2012)
Fluconazole based novel mimics containing 1,5-disubstituted 1,2,3-triazoles were synthesized by using Ru catalysed 1,3 dipolar cycloaddition. All the newly synthesized compounds and pure enantiomers were more potent than fluconazole against Candida albicans. Docking of 9A and 9B showed different conformation in the active site of Cyp51 of Candida albicans. The more active compounds 2 and 2A did not exhibit any toxicity up to 3.12 mu g mL(-1) against mammalian cell line L929.

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Alumina-supported copper iodide: an efficient and recyclable catalyst for microwave-assisted synthesis of 1,4-disubstituted 1,2,3-triazoles via three-component reaction in water - Agalave, Sandip G.; Pharande, Shrikant G.; Gade, Swapna M.; Pore, Vandana S. (Asian Journal of Organic Chemistry, 2015)
A one-pot procedure for the synthesis of 1,4-disubstituted 1,2,3-triazoles by a three-component reaction of allyl or benzyl halides, sodium azide, and terminal alkynes over a neutral alumina-supported copper iodide catalyst has been developed. The products were isolated by simple filtration followed by washing of the catalyst with acetone. The products were obtained in almost pure form in up to 98% yield (TON 495). The catalyst can be recycled for more than eight subsequent reactions. The halides are directly converted into triazoles via in situ formation of azides and thus handling of hazardous azides can be avoided. The broad scope of this protocol is shown by the synthesis of a variety of diversely substituted 1,2,3-triazoles and also two-component azide-alkyne click reaction. The key features of this procedure are the use of water as a solvent, recyclability of the catalyst up to eight runs without appreciable loss of activity, and high yields of products. The catalyst has been fully characterized by FTIR, solid-state NMR and EDX spectroscopy, ESEM, TGA, and XRD.
Keywords: 1; 2; 3-triazoles; 4; copper(I) iodide; Cycloaddition; disubstituted 1; Microwave chemistry; supported catalysts

Bile acid hydrazides: gelation, structural, physical and spectroscopic properties - Pore, Vandana S.; Agalave, Sandip G.; Pharande, Shrikant G.; Patil, Prashant A.; Kotmale, Amol S. (New Journal of Chemistry, 2015)
Synthesis and gelation properties of a series of novel bile acid hydrazides are presented. These compounds are found to undergo self-assembly leading to organogelation in certain organic solvents. Compound 1 was found to be the most ``effective'' gelator in this series. The properties of this gel have been thoroughly investigated by conventional methods typical for molecular gel studies. Sol gel transition temperature (T-g) of chloroform gels of compounds 1 and 3 was found to increase with increase in the chain length. Sol-gel transition was probed using the isothermal time test and results show that there is instantaneous increase in both the moduli after shear melting, which suggests that the kinetics of formation of the network was very fast. IR and NMR studies revealed hydrogen bonding between amidic carbonyl in the side chain and hydroxyl groups of cholic acid.

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Design and synthesis of new fluconazole analogues - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I. (Organic & Biomolecular Chemistry, 2015)
We have synthesized new fluconazole analogues containing two different 1,2,3-triazole units in the side chain. The synthesis of new amide analogues using a variety of acids is also described. All the compounds showed very good antifungal activity. A hemolysis study of the most active compounds 6e and 13j showed that both compounds did not cause any hemolysis at the dilutions tested. These compounds did not exhibit any toxicity to L929 cells at MIC and lower concentrations. In the docking study, the overall binding mode of 6e and 13j appeared to be reasonable and provided a good insight into the structural basis of inhibition of Candida albicans Cyp51 by these compounds.

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.